Breakthrough Invasive Fungal Infection After Coadministration of Venetoclax and Voriconazole. (16th March 2023) - Hall, Victoria G; Tang, Kenny; Kumar, Deepali; Rotstein, Coleman; Chow, Signy; Chan, Steven M; Husain, Shahid; Hosseini-Moghaddam, Seyed M
Abstract: Venetoclax requires a 75% dose reduction when coadministered with voriconazole. In a 10-year historical cohort of treatment with venetoclax, we did not observe a worse hematologic outcome in patients who received voriconazole prophylaxis versus those who did not. Subtherapeutic voriconazole levels and a triazole exposure history may contribute to breakthrough invasive fungal infection.